A temperature and electric field-responsive flexible smart film with full broadband optical modulation. Issue 5 (13th July 2017) - Liang, Xiao; Guo, Shumeng; Chen, Mei; Li, Chenyue; Wang, Qian; Zou, Cheng; Zhang, Cuihong; Zhang, Lanying; Guo, Shaojun; Yang, Huai
Abstract : This study provides a flexible multi-responsive smart film with a broadband optical modulation containing tin doped indium oxide nanocrystals and a phase-separated liquid crystal-polymer. Abstract : This study provides a new procedure for the preparation of a flexible multi-responsive smart film containing tin-doped indium oxide nanocrystals and a phase-separated liquid crystal-polymer. This film can reversibly control the passage of visible light in response to temperature and electric field and also screen near infrared light.